2015
DOI: 10.1007/s13311-015-0355-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies in Fragile X Syndrome: From Bench to Bedside and Back

Abstract: Fragile X syndrome (FXS), an inherited intellectual disability often associated with autism, is caused by the loss of expression of the fragile X mental retardation protein. Tremendous progress in basic, preclinical, and translational clinical research has elucidated a variety of molecular-, cellular-, and system-level defects in FXS. This has led to the development of several promising therapeutic strategies, some of which have been tested in larger-scale controlled clinical trials. Here, we will summarize re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 233 publications
(323 reference statements)
1
89
0
1
Order By: Relevance
“…Both allopregnanolone and ganaxolone hold promise to treat FXSDs, and studies with gaboxidol are planned. It is important to remark that other agents that indirectly influence the GABA deficits in FXS include the IGF-1 analogue, which is currently undergoing multicenter trials in FXS [133, 134], and cannabinoids [135], for which trials will begin soon in FXS. It is likely that GABAergic agents will continue to be part of a multimodality treatment for FXSDs for many years to come.…”
Section: Discussionmentioning
confidence: 99%
“…Both allopregnanolone and ganaxolone hold promise to treat FXSDs, and studies with gaboxidol are planned. It is important to remark that other agents that indirectly influence the GABA deficits in FXS include the IGF-1 analogue, which is currently undergoing multicenter trials in FXS [133, 134], and cannabinoids [135], for which trials will begin soon in FXS. It is likely that GABAergic agents will continue to be part of a multimodality treatment for FXSDs for many years to come.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and treatment of the medical problems in FXS are described here and the treatment of behavioral problems are described elsewhere including the use of targeted treatments to reverse the cognitive and behavioral problems (147,148). Many of the medical problems in FXS, such as OM, MVP, GERD, hernias, joint dislocation, and flat feet are related to the connective tissue problems inherent in the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The mGluR theory of FXS states that lack of FMRP allows mGluR-mediated LTD to become hyperactive, and thus lead to features associated with FXS. This theory has been validated through observed defects at the cellular level and correlating these with behavioral abnormalities across multiple animal models (4). Moreover, studies in Fmr1 KO mice with partial reduction of mGluR expression showed correction of many of these abnormalities further demonstrating mGluRs play a significant role in the pathophysiology of FXS (20).…”
Section: Metabotropic Glutamate Receptor 5 (Mglur) Antagonistsmentioning
confidence: 90%
“…Above this threshold, the gene becomes methylated and silenced, resulting in significantly reduced or absent levels of the FMR1 gene product (FMRP). FMRP is a RNA-binding protein that is heavily expressed in neurons (2,3), and functions in the stability, localization, and translation of select mRNAs (4).…”
Section: Introductionmentioning
confidence: 99%